(untitled) (Mustansiria Dental Journal, 2024)
Aim: To determine centering ability of variety of instruments and techniques used to over-instrument simulated tiny curved canals. Method: Standardized eighty blocks of clear resin, each had a canal of 20 mm in length, the straight portion was 17 mm in length, while the length of the curved apical portion was 3 mm, with a curvature of 20˚ and a radius of 4 mm, its size was equal to no.8 .02 ISO K-file, the resin blocks were divided into 8 groups, six of them were over instrumented by 1mm using hand SS K-files and Ni-Ti K-files in step back technique, Gates-Glidden drills and hand SS K-files and Ni-Ti K-files in hybrid technique, ProTaper and ProFile rotary file system in crown down technique, while two groups were under instrumented by 1 mm using hand SS K-files in step back technique and ProTaper rotary file system in crown down technique. Results: Regarding Centering ability for Over-instrumentation techniques, there was a significant difference at p < 0.05 in favor of crown down technique, in favor of Ni-Ti over the SS, and in favor of rotary instruments over the hand instruments. For under-instrumentation groups, there was a significant difference at p < 0.05 with in favor of hand SS instruments in step back technique over the rotary Ni-Ti instruments in crown down technique. Also there was a significant difference between the over and under instrumentation techniques at p < 0.05, with in favor of under instrumentation techniques. Conclusion: Within the limitations of this in vitro study, crown down technique gave better results than step back and hybrid technique, as well Ni-Ti instruments performed better than SS instruments. Rotary instruments had less deviation than the hand instruments when used inside simulated tiny curved resin canals.